Acclimatization of In Vitro Banana Seedlings Using Root-Applied Bio-Nanofertilizer of Copper and Selenium - Tarek A. Shalaby; Said M. El-Bialy; Mohammed E. El-Mahrouk; Alaa El-Dein Omara; Hossam S. El-Beltagi; Hassan El-Ramady (Agronomy, 2022)
The production of in vitro banana transplants has become an important practice in the global banana production. Proper and enough nutrients are needed for banana production particularly during the acclimatization period. To avoid the environmental problem resulting from the chemical fertilizers, nanofertilizers of Se and Cu were separately applied during the acclimatization of banana. The biological form of nano-Cu (50 and 100 mg L−1) and nano-Se (25, 50, 75, and 100 mg L−1) were studied on acclimatized banana transplants under greenhouse conditions. Both applied nanofertilizers enhanced the growth of transplant by 10.9 and 12.6% for dry weight after nano-Se and nano-Cu application up to 100 mg L−1, respectively. The survival rate was also increased by increasing applied doses of both nanofertilizers up to 100 mg L−1, whereas the highest survival rate (95.3%) was recorded for nano-Cu. All studied photosynthetic pigments and its fluorescence were improved by applying nanofertilizers. Studied antioxidant enzymatic activities (CAT, PPO, and POX) were also increased. A pH decrease in the growing medium was noticed after applying nano-Cu, which may explain the high bioavailability of studied nutrients (N, P, K, Cu, Fe, Se, and Zn) by banana transplants.